Evaluation of Multiple Ability (K-6) Beginning Teacher Competencies. For Class B Certification in Elementary Education, Early Childhood Education, and Mild Disabilities - Ellis, Edwin S. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1993)
Elementary teachers should possess the full range of competencies necessary to meet the needs of students with and without disabilities. Elementary educators should thus be eligible for certification in Elementary Education, Early Childhood Education, and Special Education (Mild Disabilities). This study created a list of competencies that is sufficiently encompassing for preparing teachers for this certification yet minimally redundant. The list was developed using three primary data sources: master teachers' perceptions of essential competencies, university course objectives, and empirical research. These competencies were then assimilated to produce a final master list. A teacher education program incorporating these competencies is presented, involving a 78-hour sequence of interrelated education courses in five semesters. An appendix lists the teacher competencies for a K-6 multiple ability program. The competencies address the following areas: (1) professionalism (teaching as a profession, the nature of schools, and the teacher as a professional); (2) the learner (human growth and development, diversity, family/parental influences, and evaluation of learner characteristics and factors affecting the learner); (3) communication and collaboration (basic communicative competence, interacting with professionals, developing educational plans, and interacting with parents); and (4) facilitating learning (assessment of instruction, evaluation of programs, instructional design and delivery, content areas, behavior management, and classroom management). (JDD)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Competence; Competency Based Teacher Education; Elementary Education; Elementary School Teachers; Higher Education; Mainstreaming; Mild Disabilities; Preservice Teacher Education; Special Education; Student Educational Objectives; Teacher Certification; Teacher Education Curriculum; Reports, Evaluative